The Genetic Architecture of Nitrogen Use Efficiency in Switchgrass (Panicum virgatum L.) - Shrestha, Vivek; Chhetri, Hari B.; Kainer, David; Xu, Yaping; Hamilton, Lance; Piasecki, Cristiano; Wolfe, Ben; Wang, Xueyan; Saha, Malay; Jacobson, Daniel; Millwood, Reginald J.; Mazarei, Mitra; et al. (Frontiers in Plant Science, 2022)
Switchgrass (Panicum virgatum L.) has immense potential as a bioenergy crop with the aim of producing biofuel as end goal. Nitrogen (N) related sustainability traits such as nitrogen use efficiency (NUE) and nitrogen remobilization efficiency (NRE) are important factors affecting switchgrass quality and productivity. Hence, it is imperative to develop nitrogen use efficient switchgrass accessions by exploring the genetic basis of NUE in switchgrass. For that, we used 331 diverse field-grown switchgrass accessions planted under low and moderate N fertility treatments. We performed a genome wide association study (GWAS) in a holistic manner where we not only considered NUE as a single trait but also used its related phenotypic traits such as total dry biomass at low N and moderate N, and nitrogen use index such as NRE. We have evaluated the phenotypic characterization of the NUE and the related traits, highlighted their relationship using correlation analysis and identified the top ten nitrogen use efficient switchgrass accessions. Our GWAS analysis identified 19 unique single nucleotide polymorphisms (SNPs) and 32 candidate genes. Two promising GWAS candidate genes, caffeoyl-CoA O-methyltransferase (CCoAOMT) and alfin-like 6 (AL6) were further supported by linkage disequilibrium (LD) analysis. Finally, we discussed the potential role of nitrogen in modulating the expression of these two genes. Our findings have opened avenues for the development of improved nitrogen use efficient switchgrass lines.